Early Parkinson's disease symptoms in α-synuclein transgenic monkeys. (30th December 2014) - Niu, Yuyu; Guo, Xiangyu; Chen, Yongchang; Wang, Chuan-En; Gao, Jinquan; Yang, Weili; Kang, Yu; Si, Wei; Wang, Hong; Yang, Shang-Hsun; Li, Shihua; Ji, Weizhi; et al.
Abstract: Parkinson's disease (PD) is an age-dependent neurodegenerative disease that can be caused by genetic mutations in α-synuclein (α-syn) or duplication of wild-type α-syn; PD is characterized by the deposition of α-syn aggregates, indicating a gain of toxicity from accumulation of α-syn. Although the major neuropathologic feature of PD is the degeneration of dopaminergic (DA) neurons in the substantia nigra, non-motor symptoms including anxiety, cognitive defect and sleep disorder precede the onset of motor impairment, and many clinical symptoms of PD are not caused by degeneration of DA neurons. Non-human primate models of PD are important for revealing the early pathology in PD and identifying effective treatments. We established transgenic PD rhesus monkeys that express mutant α-syn (A53T). Six transgenic A53T monkeys were produced via lentiviral vector expressing A53T in fertilized monkey eggs and subsequent embryo transfer to surrogates. Transgenic A53T is expressed in the monkey brain and causes age-dependent non-motor symptoms, including cognitive defects and anxiety phenotype, without detectable sleeping disorders. The transgenic α-syn monkeys demonstrate the specific early symptoms caused by mutant α-syn and provide insight into treatment of early PD.